Matrix methods : theory, algorithms and applications : dedicated to the memory of Gene Golub - Olshevsky, Vadim, 1961-; Tyrtyshnikov, E. E. (Evgeniĭ Evgenʹevich) (World Scientific, 2010)
Compared to other books devoted to matrices, this volume is unique in covering the whole of a triptych consisting of algebraic theory, algorithmic problems and numerical applications, all united by the essential use and urge for development of matrix methods. This was the spirit of the 2nd International Conference on Matrix Methods and Operator Equations from 23-27 July 2007 in Moscow that was organized by Dario Bini, Gene Golub, Alexander Guterman, Vadim Olshevsky, Stefano Serra-Capizzano, Gilbert Strang and Eugene Tyrtyshnikov. Matrix methods provide the key to many problems in pure and appl.